Telebreastfeeding and its contribution to solving breastfeeding problems in times of COVID 19 in a hospital in Huancayo 2022. - Poma Salinas , Jenny Giovanna (2023)
Objective: To establish the relationship that exists between tele-lactation and its contribution in solving breastfeeding problems in mothers recruited by the lactation clinic in a Level III hospital in times of covid-19 Huancayo-2022. Material and methods: Study Basic correlational, non-experimental design, the sample made up of 100 mothers who received tele-breastfeeding. Results: 47.4% received excellent care, 77.3% are between 20 and 35 years old, 71.1% have normal nipples, 91.7% used formulas from birth, 71.3% were not born prematurely, 88.6% resolved tele-lactation their problems. Conclusions: Telebreastfeeding contributed to solving breastfeeding problems by 88.6% in times of COVID 19.